Rancang Bangung Sistem Pengaduan Masyarakat Berbasis Progressive Web App (PWA) - Elsen, Rickard; Nurohman, Ilman (Jurnal Algoritma, 2025)
Complaints are an important part of village governance as a means for the community to convey their aspirations, complaints, and reports related to public services. In some areas, the complaint process is still carried out manually due to limited digital infrastructure, resulting in slow handling and poor documentation. This study aims to develop a Progressive Web App (PWA)-based public complaint system that can still be used even without an internet connection, utilizing Service Worker, Cache API, and IndexedDB technologies. The system was developed using the Rational Unified Process (RUP) approach with the stages of inception, elaboration, construction, and transition. System modeling used Unified Modeling Language (UML) to describe the process flow. The programming language used is Hypertext Preprocessor (PHP). Testing was conducted using the black box method and the System Usability Scale (SUS). The test results showed a SUS score of 73.3, which falls into the “Good” category. This research resulted in a public complaint system that continues to function even without an internet connection, so that complaints made by the public can still be sent without being constrained by the internet network.